(untitled) - Walesh, Stuart G. (Harlow, Essex, 2017)
This first edition of Introduction to Creativity and Innovation for Engineers was primarily designed for engineering students interested in acquiring knowledge, skills, and attitudes (KSA) that will help them be more creative and innovative. While intended primarily for engineering students, the widely applicable principles, ideas, tools, and methods introduced will also be useful for practicing engineers and as well as members of other disciplines.
Keywords: Đổi mới công nghệ,Technological innovations